Espectro de Radición Electromagnético de Esmeraldas Colombianas bajo radiación Neutrónico - Sarta Fuentes, José Antonio (Ingeniería, 1999)
Actually there are several methods which are different to traditionally established, which can modify physical properties to gem stones. These techniques require procedure which need equipment of high technology such as gamma sources with high level of irradiation, accelerators of electrons and nuclear reactors. Recently some laboratories in the world have been researched different kind of gems. This paper shows some results of recently researches using Columbian emeralds, which have been irradiated with neutrons into a nuclear research reactor.